The impact of error of refraction and retinal nerve fiber layer thickness on cognitive functions in adults with bilateral myopia. (4th March 2023) - Hussein, Mona; Ibrahim, Sahar; Taha, Ahmed; Magdy, Rehab
Abstract: Objective: Myopia is considered one of the main causes of visual impairment with increased prevalence. The main objective of this study was to evaluate and characterize cognitive impairment in adult patients with bilateral myopia, in relation to retinal nerve fiber layer (RNFL) thickness. Methods: Forty patients with bilateral myopia aged 18–40 years, and 40 age- and gender-matched healthy controls were included in the study. For all subjects, cognitive functions were assessed by Paced Auditory Serial Addition Test (PASAT) and Paired Associate Learning test (PALT). Optical coherence tomography (OCT) was done for all included patients and controls. Results: Among the myopic group, 15 patients had mild myopia, 8 patients had moderate myopia and 17 patients had high myopia. There were significant differences between patients and control groups in terms of cognitive performance and RNFL thickness. There was a significant correlation between the scores of cognitive tests and error of refraction and RNFL thickness. Conclusion: Adults with bilateral myopia have cognitive impairment, regarding information processing speed and episodic memory. Cognitive impairment is associated with retinal thinning and a higher degree of myopia.